Clinical Prognosis in Patients with Heart Failure and Reduced Left Ventricular Ejection Fraction after Myocardial Revascularization on the Background of Taking SGLT2 Inhibitors - Kucheriava, Mariia V.; Mankovsky, George B.; Rudenko, Nadiya M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To evaluate clinical and prognostic effects of sodium-glucose co-transporter 2 (SGLT2) inhibitors on primary (progression of heart failure, rehospitalization) and secondary endpoints (death from cardiovascular disease and from all causes) in patients with heart failure with reduced ejection fraction (HFrEF) within 8 months after percutaneous coronary intervention (PCI). Materials and methods. In a one-center study on the basis of the Ukrainian Children’s Cardiac Center, Clinic for Adults we analyzed the data for drug and interventional treatment of 166 patients with coronary artery disease and reduced left ventricular ejection fraction (LVEF) (<40%), who underwent PCI in the last 8 months. Among the 166 patients studied, 86 (51.8%) patients received SGLT2 inhibitors as an adjunct to the standard baseline therapy, and 80 (48.2%) patients did not receive SGLT2 inhibitors after PCI. Results and discussion. The primary combined outcome was observed in 10 patients (6.02%) in the group of patients taking SGLT2 inhibitors and 35 patients (21.08%) without addition of SGLT2 inhibitors (hazard ratio 0.72; 95% CI, 0.65-0.85; p <0.001). The incidence of the secondary combined result was lower in the group receiving SGLT2 inhibitors than in the comparison group (risk ratio, 0.85; 95% CI, 0.75-0.95; p <0.001). Conclusions. The use of SGLT2 inhibitors in addition to the standard therapу provided a 72% reduction in the relative risk, estimated by the incidence of primary combined endpoint in particular, hospitalization due to the heart failure decompensation by 34% in the same group, and the secondary endpoint by 50%. The advantage of SGLT2 inhibitors over the standard therapy in the effect on the primary endpoint did not depend on the complete or incomplete myocardial revascularization by PCI in patients over an 8-month follow-up period. SGLT2 inhibitors use in patients after PCI with reduced left ventricular systolic function over the 8-month follow-up period led to regression of angina according to the KCCQ-TSS questionnaire, decreased functional class according to the New York classification, and increased LVEF.